2008
DOI: 10.1177/0731684408089514
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Dynamic Properties of Composites in Vibration by Means of a Non-contact Mechanism

Abstract: When dynamic properties of structures in vibration are considered, their elastic modulus and damping properties are emphasized. One of the best ways for true measurement of damping is the use of a beam with free-free end conditions. The aim of this study is to investigate dynamic properties of composites by using the vibrating beam technique. The composite specimens with free-free end conditions were vibrated at their fundamental nodes. An electro-magnetic shaker was used to vibrate the specimens by means of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…An alternating current through one coil was used as vibrators whilst the motion of the other coil as transducer. The composite specimen with high flexural modulus lowers specific damping capacity [16]. From the above review, it is concluded that the work presented in this paper has not been done anywhere in the past.…”
Section: Introductionmentioning
confidence: 90%
“…An alternating current through one coil was used as vibrators whilst the motion of the other coil as transducer. The composite specimen with high flexural modulus lowers specific damping capacity [16]. From the above review, it is concluded that the work presented in this paper has not been done anywhere in the past.…”
Section: Introductionmentioning
confidence: 90%
“…An instrumented impact hammer was used to hit the specimen, and the response signal was sensed and measured by the accelerometer and the data acquisition card (DEWESoft, Dewteron Corp., Austria); the observed data were then transmitted to a PC where the natural frequencies were determined. Further, the loss factors, η were estimated by the half power bandwidth method, used elsewhere 17–25 ; the expression for the same is as follows
Figure 4.Schematic representation of impulse testing.
…”
Section: Experimental Vibration Analysismentioning
confidence: 99%